Educational-Stage Profiles of Learners’ Trust in Artificial Intelligence Across Secondary and Higher Education Contexts - Fredi Ganda Putra; Khoirunnisa Imama (AI and Developmental Insights in Education, 2026)
Trust in artificial intelligence (AI) is increasingly relevant to educational technology adoption, yet evidence remains limited on how learners at different educational stages evaluate AI systems. This cross-sectional survey examined AI trust among 412 students from secondary schools and universities in Lampung Province, Indonesia. The study assessed AI trust, AI literacy, prior AI experience, perceived AI transparency, and perceived institutional AI integration policy. Descriptive analyses, independent-samples t-tests, hierarchical multiple regression, bootstrapped mediation, and moderated mediation were used to estimate educational-stage differences and conditional indirect associations. Higher education students reported higher composite AI trust than secondary school students (M = 70.63 vs. M = 57.04, p < .001, d = 1.21). AI literacy and perceived transparency were positively associated with AI trust after controlling for gender, educational stage, and prior AI experience. Perceived transparency partially accounted for the association between AI literacy and trust (indirect effect = 0.17, 95% CI [0.11, 0.24]), and institutional AI integration policy strengthened the AI literacy-transparency pathway. Because the design was cross-sectional and based on self-report data, the findings should be interpreted as associational rather than causal or developmental evidence. The study suggests that AI literacy curricula should explicitly develop learners’ ability to evaluate transparency, uncertainty, and appropriate reliance when using AI-supported educational tools.